Leadership around the clock: Balancing caregiving and chairing - Nadine A Hartig; Kenna Colley; Melissa Grim (Academic Chairpersons Conference Proceedings, 2016)
Are you reading this abstract while texting to make sure your kids got off the bus ok or your elders took their medications today? If yes, this session is for you! We will discuss finding balance in a “lean in” culture, the effect of role strain and depletion fatigue, and how to generate self-compassion while juggling it all-or at least some of it. We will share strategies to make peace with your individual career trajectory, embrace the multiple purposes in your life, and survive the chaos.
Keywords: family and work life balance; life stress; role strain; fatigue; dual income households; caregiving; leadership; faculty personal development